Insurance Companies Adapting to Trends by Adopting Medical Tourism. Issue 4 (October 2017) - Paul, David P.; Barker, Tyler; Watts, Angela L.; Messinger, Ashley; Coustasse, Alberto
Abstract : Health care costs in the United States are rising every year, and patients are seeking new ways to control their expenditures and save money. Going abroad to receive health care is a cheaper alternative than receiving the same or similar care at home. Insurance companies are beginning to realize the benefits of medical tourism for both themselves and their beneficiaries and have therefore started to introduce medical tourism plans for their clients as an option for their beneficiaries. This research study explores the benefits and risks of medical tourism and examines the US insurance market's reaction to the trend of increasing medical tourism. The US medical tourism industry mirrors that of the United Kingdom in recent years, with more patients seeking care abroad than in the United States. Insurance companies have introduced new plans providing the option of traveling abroad to countries such as India and Costa Rica. Medical tourism is gaining popularity with US residents, and insurance companies are recognizing this trend.